Technological advancements for the treatment of steel industry wastewater: Effluent management and sustainable treatment strategies. (10th January 2023) - Rawat, Akash; Srivastava, Ashish; Bhatnagar, Amit; Gupta, Ashok Kumar
Abstract: Steel manufacturing consumes a large quantity of water for processing and cooling purpose and consequently discharges a large quantity of wastewater containing an array of recalcitrant contaminants. This review paper endeavors to summarize the steel manufacturing pathways, sources of wastewater in the steel industry, and the effectiveness of the existing treatment facilities. In addition, the efficacy and feasibility of emerging technologies with a focus on integrated treatment techniques have been discussed in detail in this review. It is evident from the reviewed literature that the advanced oxidation processes (AOPs) exhibited higher efficacy in removing recalcitrant contaminants (heavy metals >95% and phenol >99%), but the economy and scaling up are the major limitations that restrict its industrial-scale application. It was found that the combinations of a series of biological reactors facilitated better control over the microbial community and operational parameters than single-step biological processes thus improving process efficiency (COD >90%). Moreover, the integration of membranes and AOPs with biological systems can offer an economical and sustainable solution for effluent treatment and water reuse. However, the limitations of aforesaid treatment facilities open up myriad research opportunities. Attention has been given to highlighting the potential of waste utilization at steel manufacturing plants in the form of adsorbents and aggregates to be used as a valuable resource. A particular focus has been laid on sustainable practices and techno-economic aspects to help in decision-making for adopting the best available technology for effluent management in the steel industry keeping in mind future growth. Graphical abstract: Image 1 Highlights: Effluent from steel industry is complex due to presence of recalcitrant pollutants. Physicochemical treatment can effectively remove heavy metals (>96%). Biological treatment is necessary to treat large volume of effluent generated. Multistep biological treatment effectively removes organics and nutrients. Slag generated from steel manufacturing can be sustainably utilized as adsorbents.